An examination of sexual assault kit submission efficiencies among a nationally representative sample of law enforcement agencies - Hendrix, Joshua A. (Criminal justice policy review, 2020)
Drawing on results from a survey of 321 law enforcement agencies, we assess how labor and capital inputs, evidence policies, and other agency characteristics affect the number of sexual assault kits (SAKs) submitted to crime laboratories for testing. We examine to what extent agencies are submitting the maximum number of SAKs possible, given their available resources. Stochastic frontier models are used to analyze the productivity of labor inputs for the submission of SAKs and the extent to which resource inefficiencies contribute to unsubmitted SAKs. Results indicate that agencies are submitting fewer than 60% of SAKs that are possible given their resources. Full-time sworn officers were found to be productive inputs, as the number of SAKs submitted increases by 24% for every 100% increase in the number of officers. Findings also suggest that the accumulation of SAKs is driven partially by technical inefficiencies but more so by a lack of resources.